Wilhelm Waldeyer—An Important Scientific Researcher of the 19th Century in the Context of His Memoirs and Major Monographies - Scheuerlein, Hubert; Pape-Köhler, Carolina; Köckerling, Ferdinand (Frontiers in Surgery, 2021)
Wilhelm Waldeyer was one of the most important anatomists of his time. The year 2021 marks the 100th anniversary of his death. His name not only lives on in terms such as "Waldeyer's pharyngeal ring" or "Waldeyer's fascia", he also coined the terms "neuron" and "chromosome". He produced monumental monographies such as "The Pelvis" and "Ovary and Egg". Waldeyer's legacy is a large body of lifetime work that continues to impress to this day. However, he also published works that today would be described as racist. His view of a woman’s role was and is also controversial. Nevertheless, reading his autobiography (Lebenserinnerungen) today is still beneficial because it vividly illustrates the academic life and a scholarly existence of that era.